High flow nasal cannula vs non-invasive ventilation in pediatric ARDS: an RCT - Dr. Surabhi Chandra; Dr. Vijayshri; Dr. Aditi Gupta; Dr. Pratishtha Goyal; Dr. P.L. Prasad (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Pediatric Acute Respiratory Distress syndrome (PARDS) has been re-defined (2015) as per the final recommendations of the Pediatric Acute Lung Injury Consensus Conference. The use of high flow nasal cannula is a promising treatment but its efficacy compared with non invasive ventilation (NIV) is not known. Aims and Objectives: The current study was undertaken to study the efficacy of high flow nasal cannula compared with NIV in PARDS. Methods: This was a pilot randomized controlled trial done in the PICU of a tertiary care teaching hospital over 10 months (December 2017 – September 2018). All patients aged 1-18 years of age, who presented with or developed ARDS during their course of hospitalization, and who fulfilled the inclusion criteria, were randomized to receive HFNC and Continuous Positive Airway Pressure (NIV) as the initial respiratory support.Details were noted in a pre-designed standardized data collection form, entered into MS-EXCEL worksheet 2013 and analyzed using the Epi info software version 7.2.0.1. Results: A total of 40 patients were enrolled, 20 in each arm.Of these majority (25/40=62.5%) were boys. Majority of these patients were from rural or semi-urban areas (28/40=70.0%) and belonged to low socio-economic class (33/40= 82.5%) patients.Underlying diagnosis was sepsis in the majority (27/40=67.5%) patients.Twenty one (23/40=57.5%) patients had co-existent pneumonia.Development of hemodynamic instability approached statistical significance in being low in HFNC group compared with the CPAP group (p=0.07; OR 0.206, 95% CI 0.036-0.159).Subsequent requirement of invasive ventilation was also low in HFNC group compared with CPAP group and approached significance (p=0.09; OR 1.653, 95% CI 0.074-1.246). Total duration of respiratory support (p=0.62) was comparable in both the groups. Conclusion: HFNC is efficacious in managing PARDS. Subsequent requirement of invasive ventilation and hemodynamic deterioration was significantly low with HFNC compared with NIV (CPAP).